Therapeutic antibodies for COVID-19: is a new age of IgM, IgA and bispecific antibodies coming? - Jingjing Zhang; Han Zhang; Litao Sun (mAbs, 2022)
Early humoral immune responses to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are dominated by IgM and IgA antibodies, which greatly contribute to virus neutralization at mucosal sites. Given the essential roles of IgM and IgA in the control and elimination of SARS-CoV-2 infection, the mucosal immunity could be exploited for therapeutic and prophylactic purposes. However, almost all neutralizing antibodies that are authorized for emergency use and under clinical development are IgG antibodies, and no vaccine has been developed to boost mucosal immunity for SARS-CoV-2 infection. In addition to IgM and IgA, bispecific antibodies (bsAbs) combine specificities of two antibodies in one molecule, representing an important alternative to monoclonal antibody cocktails. Here, we summarize the latest advances in studies on IgM, IgA and bsAbs against SARS-CoV-2. The current challenges and future directions in vaccine design and antibody-based therapeutics are also discussed.